Large Screening Identifies ACE2 Positively Correlates With NF-κB Signaling Activity and Targeting NF-κB Signaling Drugs Suppress ACE2 Levels - Yan, Meichen; Dong, Yuan; Bo, Xuena; Cheng, Yong; Cheng, Jinbo (Frontiers in Pharmacology, 2021)
Coronaviruses SARS-CoV-2 infected more than 156 million people and caused over 3 million death in the whole world, therefore a better understanding of the underlying pathogenic mechanism and the searching for more effective treatments were urgently needed. Angiotensin-converting enzyme 2 (ACE2) was the receptor for SARS-CoV-2 infection. In this study, we found that ACE2 was an interferon-stimulated gene (ISG) in human cell lines. By performing an ISG library screening, we found that ACE2 levels were positively regulated by multiple ISGs. Interestingly, ACE2 levels were highly correlated with ISGs-induced NF-κB activities, but not IFNβ levels. Furthermore, using an approved clinical durgs library, we found two clinical drugs, Cepharanthine and Glucosamine, significantly inhibited ACE2 level, IFNβ level, and NF-κB signaling downstream TNFα and IL6 levels. Our finding suggested the possible inhibitory effects of Cepharanthine and Glucosamine during SARS-CoV-2 infection and the subsequent inflammatory cytokine storm.